2010
DOI: 10.1373/clinchem.2009.142810
|View full text |Cite
|
Sign up to set email alerts
|

Seven Direct Methods for Measuring HDL and LDL Cholesterol Compared with Ultracentrifugation Reference Measurement Procedures

Abstract: BACKGROUND Methods from 7 manufacturers and 1 distributor for directly measuring HDL cholesterol (C) and LDL-C were evaluated for imprecision, trueness, total error, and specificity in nonfrozen serum samples. METHODS We performed each direct method according to the manufacturer’s instructions, using a Roche/Hitachi 917 analyzer, and compared the results with those obtained with reference measurement procedures for HDL-C and LDL-C. Imprecision was estimated for 35 runs performed with frozen pooled serum spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
230
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(245 citation statements)
references
References 19 publications
(8 reference statements)
6
230
2
7
Order By: Relevance
“…Recently, it was reported that the Friedewald method is more appropriate for determining LDL-C values than direct methods, because of the great variability between different measuring kits. 40) However, we decided to adopt direct methods in this analysis because of the lack of a great number of total cholesterol values, which is related to the reimbursement policy in some regions. Many institutions were not allowed to measure both total cholesterol and LDL-C by direct methods during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the Friedewald method is more appropriate for determining LDL-C values than direct methods, because of the great variability between different measuring kits. 40) However, we decided to adopt direct methods in this analysis because of the lack of a great number of total cholesterol values, which is related to the reimbursement policy in some regions. Many institutions were not allowed to measure both total cholesterol and LDL-C by direct methods during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, direct methods show poor performance with high triglyceride (TG) levels [4][5][6]. An earlier review comparing direct measurement of LDL-C vs calculation of LDL recommended the use of direct LDL measurements in hypertriglyceridaemic patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…We also reported several discrepancies in LDL-C levels by the HPLC method and the CDC reference procedure using lipoprotein abnormalities, such as lipoprotein lipase deficiency, E2/2 type III hyperlipidemia, cholesteryl ester transfer protein deficiency and hyper Lp(a) lipoproteinemia 19) . In the US-Japan cooperative evaluation of current generations of homogeneous methods for measuring HDL and LDL cholesterol 20) , we have already investigated the analytical performance of seven LDL-C homogeneous assay kits using diseased (primarily dyslipidemic and cardiovascular) as well as the non-diseased individuals in the United States 20) . As expected, all the LDL-C assay methods failed to meet the goals for diseased individuals because of a lack of specificity for abnormal lipoproteins.…”
Section: Discussionmentioning
confidence: 99%